Factors influencing parents’ hesitancy to vaccinate their children aged 5–11 years old against COVID-19: results from a cross-sectional study in Malaysia - Marzo, Roy Rillera; Chakraborty, Ritankar; Soh, Shean Yih; Thew, Hui Zhu; Chong, Collins; Siau, Ching Sin; Abdul Wahab, Khairuddin Bin; Binti Ariffin, Indang Ariati; Chauhan, Shekhar; Brackstone, Ken; Padhi, Bijaya Kumar; Heidler, Petra (Frontiers Media, 2023)
Introduction: Vaccination programs have been rolled out across the globe to contain and mitigate the spread of the COVID-19 infection. Until recently, such programs were limited to adults and the older population, thereby limiting children from getting vaccinated. Recently, the Malaysian government rolled out vaccination for children aged 5–11 years. However, there are certain factors that might affect vaccination uptake among children. This study explores factors influencing parents’ hesitancy to vaccinate children in Malaysia.